Microbial populations and their contribution to suppressive soils generation - Covarrubias, Sergio Abraham; Barrera-Galicia, Guadalupe C.; Martínez-Acuña, Mónica Imelda; Cardoso-Ortiz, Jaime; Flores de la Torre, Juan Armando (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2024)
Soil is an essential resource in agroecosystems because it supports plant roots and provides nutrients for their growth. Soil is also the habitat of microorganisms that can have both beneficial and harmful effects on plants. Suppressive soils (SS) are perhaps the best example to describe the complex interaction between plants and their microbiome. In SS, the occurrence and severity of an infections remain low even under suitable conditions for their development. There are two types of suppression in SS: general suppression, which involves the collective action of the entire microbial community, and specific suppression, where certain microbial taxa or antagonistic groups are responsible for the suppression. The antagonistic effect of SS is due to several mechanisms such as: competition for nutrients, production of antimicrobial compounds, volatile organic compounds (VOCs), and induction of systemic resistance. In recent decades, thanks to omics technologies, the microbial nature of suppression has been widely demonstrated. However, enhancing the formation of suppressive soils remains a challenge in terms of sustainable management. This review aims to provide an updated overview of the role of microbial communities in the formation of suppressive soils.
Keywords: microbiome; phytopathogen; biocontrol